DEFINING THE BURNOUT LEVELS OF CORRECTIONAL OFFICERS: THE EXAMPLE OF KOCAELİ OPEN PRISON - Tülin BAYRAKTAR; Prof. Dr. Yılmaz Özkan (International Journal of Eurasia Social Sciences, 2015)
Despite the high burnout level of correctional officers so very little to almost there are no studies in the literature on burnout in this profession. This study has done for he purpose of analyzing of the professional burnout degrees of the correctional officers and investigating the causes and drawing attention to the problems of the profession. The study sample are the 99 corectional officers who work in open prisons in Kandıra-Kocaeli. In this study a questionnaire was used which was formed from two parts including demographic and burnout. The statistics datas were analyzed by IBM SPSS 20.0 software package, frequency analysis was done for the arguments in the analysis of data, for the dependent variables t-test and one-way ANOVA for dependent variables. The significance was accepted as 0.05.